2019
DOI: 10.17746/1563-0110.2019.47.2.103-111
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Remote Sensing, Geophysical Methods and Soil Analysis in the Study of Sites Disturbed by Agricultural Activity

Abstract: This study is based on an interdisciplinary approach to the prospection of archaeological sites impacted by modern agricultural plowing activity. We applied remote sensing, combined with geophysical, geochemical, and archaeological methods at Kushmanskoye III — a medieval Finno-Ugric site in the Cheptsa River basin, northern Udmurtia (9th–13th centuries AD). As a result of many years of plowing, the site cannot be visually demarcated, and visual traces of its extent have been obliterated. Scientifi c methods i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…In addition, an assessment of the saturation of the occupation layer with organic materials was carried out based on the contents of phosphates, organic carbon F I G U R E 1 Location of the studied area in Udmurt Republic and Kushman archaeological cluster (right-hand map) and magnetic susceptibility in the soil materials of the cores. In the second stage of interdisciplinary studies (Zhurbin et al, 2019), the presence of another external line of fortifications, which also has no relief features, was proven, and a reconstruction of the layout of the inner and outer parts of the settlement was proposed. An analysis of the relative position of geophysical anomalies showed that the buildings were aligned in parallel rows in the inner part of the settlement.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, an assessment of the saturation of the occupation layer with organic materials was carried out based on the contents of phosphates, organic carbon F I G U R E 1 Location of the studied area in Udmurt Republic and Kushman archaeological cluster (right-hand map) and magnetic susceptibility in the soil materials of the cores. In the second stage of interdisciplinary studies (Zhurbin et al, 2019), the presence of another external line of fortifications, which also has no relief features, was proven, and a reconstruction of the layout of the inner and outer parts of the settlement was proposed. An analysis of the relative position of geophysical anomalies showed that the buildings were aligned in parallel rows in the inner part of the settlement.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, synchronous changes in the magnetic susceptibility, phosphate content and active microbial biomass in soil samples indicate anthropogenic transformation of soils far beyond the defensive structures (Zhurbin et al, 2019). Thus, archaeological, geophysical and soil studies have revealed areas with different thicknesses of the occupation layer.…”
Section: Introductionmentioning
confidence: 99%